Access to and affordability of healthcare for TB patients in China: issues and challenges. Issue 1 (December 2016) - Tang, Shenglan; Wang, Lixia; Wang, Hong; Chin, Daniel
Abstract This paper introduces the background, aim and objectives of the project entitled "China—the Gates Foundation Collaboration on TB Control in China" that has been underway for many years. It also summarizes the key findings of the nine papers included in this special issue, which used data from the baseline survey of Phase II of the project. Data were collected from the survey of TB and MDR-TB patients, from designated hospitals, health insurance agencies and the routine health information systems, as well as key informant interviews and focus group discussions with relevant key stakeholders. Key issues discussed in this series of papers include the uses of TB services and anti-TB medicines and their determining factors related to socio-economic and health systems development; expenditures on TB care and the financial burden incurred on TB patients; and the impact of health insurance schemes implemented in China on financial protection.